Progress and Security Analysis of Quantum Cryptography Communication - Junsen Lai; Bingbing Wu; Shaohui Li; Wenyu Zhao; Haiyi Zhang (Dianxin kexue)
Quantum cryptography communication，which provided unconditional security by means of quantum key distribution and one-time pad encryption，has become one focus of communication academia and industry. The quantum key distribution protocol，devices，and network architecture were reviewed. The security loopholes and quantum hacking schemes of practical system were analyzed. Corresponding security countermeasures were summarized. Recent progress of measurement-device-independent quantum key distribution was also introduced. In the end，the security challenge，development direction and prospects of quantum cryptography communication were also discussed.